The effec of Neurotensin on intestinal ischemia reperfusion injury - Emin GÜRLEYİK,; Günay GÜRLEYİK,; İrfan CAN,; Ali ÖZCAN,; Pembegül GÜNEŞ,; İlhan ONARAN, (Turkish Journal of Gastroenterology, 2019)
-